Advocates for the Oppressed : Hispanos, Indians, Genízaros, and Their Land in New Mexico - Ebright, Malcolm (Book collections on Project MUSE., 2014)
"Struggles over land and water have determined much of New Mexico's long history. The outcome of such disputes, especially in colonial times, often depended on which party had a strong advocate to argue a case before a local tribunal or on appeal. This book is partly about the advocates who represented the parties to these disputes, but it is most of all about the Hispanos, Indians, and Genizaros (Hispanicized nomadic Indians) themselves and the land they lived on and fought for. Having written about Hispano land grants and Pueblo Indian grants separately, Malcolm Ebright now brings these narratives together for the first time, reconnecting them and resurrecting lost histories. He emphasizes the success that advocates for Indians, Genizaros, and Hispanos have had in achieving justice for marginalized people through the return of lost lands and by reestablishing the right to use those lands for traditional purposes"--